Forensic Spotlight: Innovative Latent Print Processing. - Bagley, Nicole; Brillhart, Monique (FBI Law Enforcement Bulletin, 2021)
The article presents the discussion on Latent Print Unit (LPU) at the FBI Laboratory in Quantico, Virginia for innovative latent print processing. Topics include one latent print processing technique taking a creative approach known as cyanoacrylate or superglue and fuming; material chosen due to the robust antistatic, flame-retardant, and puncture-resistant properties; and integrated sleeved ports where hoses being attached for facilitating humidification and defumigation.